2017
DOI: 10.1371/journal.pone.0172295
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Clavibacter michiganensis subspecies, pathogens of important agricultural crops

Abstract: Subspecies of Clavibacter michiganensis are important phytobacterial pathogens causing devastating diseases in several agricultural crops. The genome organizations of these pathogens are poorly understood. Here, the complete genomes of 5 subspecies (C. michiganensis subsp. michiganensis, Cmi; C. michiganensis subsp. sepedonicus, Cms; C. michiganensis subsp. nebraskensis, Cmn; C. michiganensis subsp. insidiosus, Cmi and C. michiganensis subsp. capsici, Cmc) were analyzed. This study assessed the taxonomic posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…Genome analyses of C. michiganensis subspecies have been performed since the first report of the genome sequence of C. michiganensis ssp. michiganensis strain NCPPB382 (Bentley et al, 2008;Gartemann et al, 2008;Bae et al, 2015;Lu et al, 2015b;Tambong et al, 2015;Tambong, 2017). Genomic analysis of NCPPB382 revealed that it has a 130 kb chromosomal pathogenicity island (PAI) consisting of chp and tomA subregions, which include multiple virulence genes mostly encoding enzymes such as pectate lyase, serine proteases, and tomatinase, and this PAI region has been shown to play an important role in invasion of the host plant (Eichenlaub & Gartemann, 2011;Jackson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Genome analyses of C. michiganensis subspecies have been performed since the first report of the genome sequence of C. michiganensis ssp. michiganensis strain NCPPB382 (Bentley et al, 2008;Gartemann et al, 2008;Bae et al, 2015;Lu et al, 2015b;Tambong et al, 2015;Tambong, 2017). Genomic analysis of NCPPB382 revealed that it has a 130 kb chromosomal pathogenicity island (PAI) consisting of chp and tomA subregions, which include multiple virulence genes mostly encoding enzymes such as pectate lyase, serine proteases, and tomatinase, and this PAI region has been shown to play an important role in invasion of the host plant (Eichenlaub & Gartemann, 2011;Jackson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Population genetic and comparative genomic analyses are imperative components for the development of robust and specific diagnostic tools (5,26,27,28). Multiple genome alignments using Mauve software resulted in highly conserved and unique gene regions specific for C. michiganensis in general (major facilitator superfamily gene) and specifically for C. m. subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, primer set CM-dnaA-F/R, designed to amplify the dnaA partial-gene sequence of C. michiganensis, was used to confirm the identity of all nine subspecies (S1 Table). The housekeeping dnaA gene has been proven as a potential genetic marker for plant bacterial phylogenetic studies and identity confirmation [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Michiganens infection. The genome of Cmm strain NCPPB382 ( Cmm382 ) identified the chp/tomA 129‐kb pathogenicity island that harbors serine proteases, cell wall degrading enzymes, and a tomatinase enzyme . Virulence factors involved in uptake and metabolism of carbohydrates and glycosyl hydrolases were in the tomA regions in the genome and in two plasmids (pCM1 and pCM2) .…”
mentioning
confidence: 99%